BRIDGING WORLDS: WHEN LOCAL CULTURE MEETS ISLAMIC VALUES IN LOCAL TRADITION MACCERA MANURUNG - Ningsih, Widya; Badollahi, Muhammad Zainuddin; Anjarsari, Hilda; Ariyani, Risma; A’yun, Dya Qurotul (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2024)
This study explores the phenomenon of Maccera Manurung, a local tradition that combines local culture with Islamic values. Through a religious anthropology approach, this study aims to understand how the relationship between local culture and Islamic values is manifested in Maccera Manurung, as well as its significance for local communities. This study used qualitative research methods by conducting in-depth interviews with religious leaders, community members, and scholars in the area who practiced Maccera Manurung. The results showed that Maccera Manurung is a unique phenomenon of religious and cultural syncretism, where local culture and Islamic values influence each other and give different meanings to local communities. On the one hand, Maccera Manurung maintains a distinctive local cultural identity, and on the other hand, opens up space for interpretation and adaptation of Islamic values relevant to local communities. The study concludes that Maccera Manurung can be seen as a form of cultural innovation and religious adaptation that results in a dynamic and evolving religious tradition. This research contributes to an understanding of the dynamics of the relationship between religion and culture in local contexts as well as yielding insights into how religious and cultural syncretism can shape unique cultural identities.